Determination of Niacin in Orange Juice with Lyophilized Lactobacillus arabinosus ATCC 8014 - Gorin, N. (1970)
The determination of niacin in orange juice with lyophilized Lactobacillus arabinosus ATCC 8014 has the advantage over the usual method in eliminating the delay caused by the necessity of cultivating cells of L. arabinosus for the inoculum and also in eliminating the periodical cultivation on agar slopes.